Use of CO2 balances to determine ventilation rates in a fattening rabbit house - Estelles, F.; Fernandez, N.; Torres, A. G.; Calvet, S. (Spanish Journal of Agricultural Research, 2011)
Determining accurately the ventilation rates from rabbits houses, using non-expensive and non-invasive methods, is needed. The main aim of this work was to test the carbon dioxide balance as a method to determine the ventilation rate in fattening rabbit farms. In addition, the CO2 release rate from rabbit manure was measured, and the effect of CO2 concentration gradient between the inlet and outlet air of the building, on the method accuracy was characterized. To these aims, a fattening rabbit farm was evaluated during two periods and CO2 concentrations were simultaneously monitored in the inlet and outlet air by using a photoacoustic monitor. Ventilation rates were also directly determined by calibration of the exhaust fans and monitoring their operation times. CO2 emissions from manure were measured during two whole fattening periods, using a flux chamber and a photoacoustic monitor. The effect of CO2 concentrations gradient between the inlet and outlet of the farm on the accuracy of the balance was studied through statistical regressions. The CO2 emission from manure resulted in 13% of total CO2 emissions (considering both manure and animals). No statistically significant differences were found between measured and calculated ventilation rates. The effect of the CO2 gradient on the balance accuracy was statistically significant only in one of the trials. According to these results, the CO2 balance can be recommended for the determination of ventilation rates in fattening rabbit buildings.